36. NUTRITIONAL STATUS AND ASSOCIATED FACTORS IN CHILDREN UNDER 5 YEARS OLD IN SOME DISTRICTS OF KONTUM PROVINCE, 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the prevalence of malnutrition and associated factors in children under 5 years old in some districts of Kontum province.Method: A cross-sectional study was conducted from August to October 2022 on 360 children under 5 years old in 3 districts of Dak To, Kon Plong, and Tu Mo Rong in Kontum province. The nutritional status of children was classified according to WHO Child Growth Standards 2006. Factors associated with malnutrition were determined by medical statistical analysis.Results: The overall malnutrition rate was 40.3% for stunting, 24.2% for underweight, and 2.8% for wasting. Several factors associated with malnutrition include male gender (OR = 2.54; 95%CI 1.15-5.58), household having from 3 children (OR = 3.32; 95%CI 1.49-7.37), and the household's experience of food insecurity during the year (OR = 4.46; 95%CI 1.88-10.59).Conclusions: The rate of malnutrition in children under 5 years old in the surveyed districts is still high, according to WHO's cut-off values for public health significance. The government and relevant organizations need to pay attention to education and support activities for families to improve the nutritional status of children under 5 years old in the locality.
Keywords: Malnutrition; children under 5 years old; associated factors